2007
DOI: 10.1029/174gm11
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the post-perovskite phase with seismological observations of lowermost mantle structure

Abstract: The discovery of post-perovskite (pPv), the high pressure polymorph of (Mg x ,Fe 1-x )SiO 3 perovskite (Pv), may have profound implications for the thermal, chemical and dynamical structure of the deep Earth, if it can be demonstrated that pPv currently exists in the lower mantle. The requisite basis for such a demonstration is seismological observation of elastic velocity and density structures diagnostic of or at least compatible with the expected properties of pPv occurrence in a realistic lower mantle chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 214 publications
3
40
0
Order By: Relevance
“…At the time of the modelling of Sidorin et al (1999a, b), there were limited observations of the D″ discontinuity in the central Pacific; subsequently, studies have found that the discontinuity in this region is too shallow to be compatible with Sidorin et al's models, and this may be indicative of chemical effects on the phase boundary (e.g. Lay and Garnero 2007;Ohta et al 2008). Furthermore, Hutko et al (2006) have mapped 100-km amplitude undulations in the depth of D″ reflections over lateral distances of 200-300 km, which would require temperature variations of 500-1000 K that are geodynamically difficult to explain.…”
Section: Discontinuity Thicknessmentioning
confidence: 93%
See 1 more Smart Citation
“…At the time of the modelling of Sidorin et al (1999a, b), there were limited observations of the D″ discontinuity in the central Pacific; subsequently, studies have found that the discontinuity in this region is too shallow to be compatible with Sidorin et al's models, and this may be indicative of chemical effects on the phase boundary (e.g. Lay and Garnero 2007;Ohta et al 2008). Furthermore, Hutko et al (2006) have mapped 100-km amplitude undulations in the depth of D″ reflections over lateral distances of 200-300 km, which would require temperature variations of 500-1000 K that are geodynamically difficult to explain.…”
Section: Discontinuity Thicknessmentioning
confidence: 93%
“…References for D″ observations given in Sect. 13.3.1 in D″ structure can be ascribed to different stacking techniques, and subjective data selection between different studies (Wysession et al 1998;Lay and Garnero 2007).…”
Section: The D″ Discontinuitymentioning
confidence: 98%
“…Although our understanding of this phase transition and its implications is still at an early stage, the CaIrO 3 -type phase of (Mg,Fe)SiO 3 appears to provide some of the right characteristics to match seismic observations of D 00 (Wookey et al 2005;Lay & Garnero 2007;Shim 2008). While there remain considerable uncertainties in laboratory pressure determinations at these extreme conditions, the transformation occurs at pressures near those found at the top of the D 00 layer for expected mantle compositions (Murakami et al 2004;Oganov & Ono 2004;Wookey et al 2005).…”
Section: Overview Of the Earth's Mantlementioning
confidence: 99%
“…A seismic discontinuity marks the top of D 00 and the region itself is characterized by strong lateral heterogeneity and other anomalous properties (Garnero 2000;Lay & Garnero 2007). In contrast to the bulk of the lower mantle, the core-mantle boundary region exhibits pronounced seismic anisotropy (Kendall 2000).…”
Section: Overview Of the Earth's Mantlementioning
confidence: 99%
“…This mineral phase not only provides a compelling explanation for many of the seismic properties we observe (Hernlund et al 2005;Wookey et al 2005;Mao et al 2006;Lay & Garnero 2007;Wookey & Kendall 2007), but also provides us with some unique and exciting opportunities. Among these is the possibility of its usage as a 'geothermometer'.…”
Section: Understanding the Cmbmentioning
confidence: 99%